Defining the elusive oncogenic role of the methyltransferase TMT1B - Denford, Sarah E.; Wilhelm, Brian T. (Frontiers in Oncology, 2023)
Methyltransferases are enzymes fundamental to a wide range of normal biological activities that can become dysregulated during oncogenesis. For instance, the recent description of the methyltransferase-like (METTL) family of enzymes, has demonstrated the importance of the N 6adenosine-methyltransferase (m 6 A) modification in transcripts in the context of malignant transformation. Because of their importance, numerous METTL family members have been biochemically characterized to identify their cellular substrates, however some members such as METTL7B, recently renamed TMT1B and which is the subject of this review, remain enigmatic.First identified in the stacked Golgi, TMT1B is also localized to the endoplasmic reticulum as well as lipid droplets and has been reported as being upregulated in a wide range of cancer types including lung cancer, gliomas, and leukemia. Interestingly, despite evidence that TMT1B might act on protein substrates, it has also been shown to act on small molecule alkyl thiol substrates such as hydrogen sulfide, and its loss has been found to affect cellular proliferation and migration.Here we review the current evidence for TMT1B's activity, localization, and potential biological role in the context of both normal and cancerous cell types.List of abbreviations: thiol methyltransferase 1B (TMT1B), S-adenosyl-methionine (SAM), methyltransferase-like (METTL), N 6 -methyladenosine modification (m 6 A), endoplasmic reticulum (ER), lipid droplet (LD), tumour-node-metastasis (TNM), hydrogen sulfide (H2S), tyrosine kinase inhibitor (TKI), coding sequence (CDS), reactive oxygen species (ROS), endothelial-mesenchymal transition (EMT), fatty acid (FA)